2009
DOI: 10.1186/1550-2783-6-9
|View full text |Cite
|
Sign up to set email alerts
|

Glycine propionyl-L-carnitine produces enhanced anaerobic work capacity with reduced lactate accumulation in resistance trained males

Abstract: Background: Recent research has indicated that short term administration of glycine propionyl-L-carnitine (GPLC) significantly elevates levels of nitric oxide metabolites at rest and in response to reactive hyperaemia. However, no scientific evidence exists that suggests such supplementation enhances exercise performance in healthy, trained individuals. The purpose of this study was to examine the effects of GPLC on the performance of repeated high intensity stationary cycle sprints with limited recovery perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
(32 reference statements)
4
27
1
Order By: Relevance
“…We reported that there was a significant reduction in BL accumulation post-30-sec Wingate test. In agreement with this, Jacobs et al 31 showed a reduced BL accumulation after only short (10-s) bouts of anaerobic tests where LCR was ingested in a single dosage. A longer duration of supplementation could be speculated to buffer hydrogen ions produced by lactic acid breakdown to a greater extent, resulting in less pronounced blood acidity 2,32 .…”
Section: Discussionsupporting
confidence: 54%
“…We reported that there was a significant reduction in BL accumulation post-30-sec Wingate test. In agreement with this, Jacobs et al 31 showed a reduced BL accumulation after only short (10-s) bouts of anaerobic tests where LCR was ingested in a single dosage. A longer duration of supplementation could be speculated to buffer hydrogen ions produced by lactic acid breakdown to a greater extent, resulting in less pronounced blood acidity 2,32 .…”
Section: Discussionsupporting
confidence: 54%
“…Thus, the endurance capacity may be improved. This is consistent with the results of some previous studies 16,17 ; however, Izadi et aldid not observe significant differences in lactate concentrations. 12 Presumably, the consumption of L-tartrate and heparin could have interfered with the effects of L-carnitine.…”
Section: Discussionsupporting
confidence: 83%
“…GPLC transports fatty acids to the mitochondria for oxidation, CoQ10 is essential for adenosine-5 0 -triphosphate (ATP) production as a cofactor in the mitochondrial electron transport chain, and D-ribose is an intergral structural component of ATP. These three nutrients have been demonstrated to increase exercise capacity in humans [100][101][102][103] and equids [58,104], presumably by stimulating ATP production and recovery while supporting ATP energy substrates at the same time [105]. Daily ribose supplementation (0.07 g/kg BW, twice daily) for 14 days in the diet of exercising geldings resulted in lower blood ammonia-N and plasma lactic acid during recovery after a standardized exercise test.…”
Section: Discussionmentioning
confidence: 99%